PERHITUNGAN BEBAN RANCANGAN (DESIGN LOAD) KONSTRUKSI KAPAL BARANG UMUM 12.000 DWT BERBAHAN BAJA MENURUT REGULASI KELAS - Nur, Iswadi (Bina Teknika, 2016)
The ship’s design load to be affected by some factors such as; the inside force of ship, the outside force of ship, the kind of ship, the ship’s length, the comparison of ship’s dimension, the sea water waves, and the corrosion of steel. The design load of ship’s weather deck area (PD), the design load of ship’s bottom area (PB), although the design load of ship’s side area (PS) becomes parameter factor to calculate the ship’s construction. The subject of design load calculation is the general cargo ships with main dimension as : Loa = 131,273 m, Lpp = 122,360 m, B = 19,50 m, H = 11,138 m, T = 8,77 m, Cb = 0,74, dwt = 12.000 tons, displacement = 15.875 tons, speed = 13 knots, Cm = 0,98, Cw = 0,83, ME = 6.700 hp. The calculation of of ship’s design load had many results such as : the design load of weather deck (PD) likes; the mean of PD = 107,851 kN/m2, the PD of after peak area = 9,99 % more than the PD of middle area, because the super structures likes ; poop deck, bridge deck, navigation deck, and wheel house to be supported by the deck plate of after peak area. Also the PD of fore peak area = 64, 00 % more than the PD of middle area, because location of the deck plate of fore peak area to the fore castle deck although the windlass to be close to one another, of course the deck plate of fore peak area support both of them. The design load of ship’s bottom area (PB) likes ; the mean of PB = 126, 515 kN/m2, the PB of after peak area = 13, 93 % more than the PB of middle area, because location of the after peak bottom plate to the engine room, the propeller, although the rudder to be close to one another, of course the bottom plate of after peak area can absorb the main engine vibration, the propeller vibration, although the rudder vibration. The PB of fore peak area = 29,50 % more than the PB of middle area, because part of the bottom plate of fore peak area becomes the stem plate, and then the stem plate to be striked by the sea water waves when the ship voyage on the sea.The design load of ship’s side area (PS) likes ; the mean of PS = 98, 471 kN/m2, the PS of after peak area = 11, 53 % more than the PS of middle area, and the PS of fore peak area = 20, 80 % more than the PS of middle area. The reason of them to be same with PD although PB before. More over, the mean value of PB more than the value of PD althought PS, the deferences value to be affected by the factor of steel corrosion and the factor of sea water wave. Also the mean PS value less than the mean value of PB althought PD, the deferences value to be affected by distance of the ship’s side plate to the ship’s longitudinal netral axis to be close to one another.